Ascertaining the interaction effects among organisational citizenship behaviour, work overload and employees' performance in the Ghanaian construction industry. Issue 7 (9th September 2019) - Kissi, Ernest; Asare, Odoi Ansah; Agyekum, Kofi; Yamoah Agyemang, Daniel; Labaran, Musah
Abstract : Purpose: The purpose of this paper is to ascertain the interaction effects among organizational citizenship behavior (OCB), work overload (WO) and employees' performance in the Ghanaian construction industry, thus identifying the thin boundary between advocating OCB and avoiding WO in attempt to increase higher employee performance. Design/methodology/approach: Using a quantitative research method, three hypotheses were tested. The views of 86 project teams were elicited using a structured questionnaire, and linear regression was utilized to validate the hypotheses. Findings: The study proved that OCBs positively affect employee performance in the construction industry. The results implied that increased work load on employees do not increase their productivity levels, but adversely increase the unconsiderable effects of employees' work lives. In addition, WO played the role of homologizing moderation in the relationship between OCB and employee performance. Practical implications: The findings suggest that there is a considerable effect of WO on overall employee performance in the construction industry; thus, there is a need for stakeholders to address this issue for performance improvement. Originality/value: The application and investigation of these issues have dominated the banking industry but lacked in the construction industry. The current study therefore provides useful insight into the interaction effects among organizational citizenship behavior, WO and employees' performance in the Ghanaian construction industry.